Influence of Socio-Economic Factors on Attitude of Ethno-Botanical Users among Forest Fringe Communities in Sub-Himalayan Region of West Bengal, India - Biswakarma, S.; Pala, N. A.; Shukla, G.; Vineeta, Vineeta; Pradhan, K.; Chakravarty, S. (Indian Journal of Hill Farming, 2018)
In the present study attitude of forest fringe communities around Chilapatta reserve forest in northern part of West Bengal towards use of ethno-medicinal plants in comparison to different socio-economic factors like gender, age, income, education and material possession etc. has been addressed. The eight villages from district Alipurduar and Chilapatta forest division were purposively selected due to the availability of forest ecosystem and profuse number of people who are residing within the forest area and maintain their livelihood and fulfilling their other needs with the help of forest resources. Primarily, the purposive and random sampling procedure was followed in case of selecting the area and respondents. A total of hundred respondents were selected randomly from each village for personal semi-structured interview schedule. Amongst the respondents 91% were male and 49% were of young age (i.e. 33-52 years). Majority of the respondents (95%) were schedule tribe or belong to indigenous community, literate (71%) and farmers (68%) with medium family size (52%) and marginal (low) land holding (78%). The variable gender is positively and significantly contributing in case of characterizing the predicted variable, attitude of ethno-botanical plant users. In presence of other predictor variable, the variable gender contributes 23% in case of delineating the attitude. One unit change in the variable gender can change 1.97 units in attitude towards positive direction. The R2 value of 0.163 indicates that the eleven predictor variables put together have explained 16.30% variations embedded with the predicted variables attitude of ethno-botanical plant users. Still 83.70% variations within the predicted variable are left unexplained. This study also reported that, there is vertical transfer of ethno-botanical plant knowledge which is due to the interest among the younger generation to learn and practice it.